2010
DOI: 10.17221/126/2009-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary garlic powder on performance, egg yolk and serum cholesterol concentrations in laying quails

Abstract: ABSTRACT:This study was conducted to investigate the effects of garlic powder on the performance, egg traits, egg cholesterol and serum parameters of laying Japanese quails. One hundred and twenty 10-weeks-old quails were allocated to four dietary treatments. Quails were caged individually and fed diets supplemented with 0 (control), 1, 2, 4% garlic powder for 12 weeks. There were significant (P < 0.05) differences among the diets in feed consumption, feed efficiency and egg production as averaged over 12 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 28 publications
4
31
1
8
Order By: Relevance
“…According to Reddy et al (1991), egg production and feed efficiency were not affected during or at the end of eight weeks of feeding garlic oil to the Babcock layer. Canogullari et al (2009) fed layer diets containing 0, .5, 1 and 2% garlic powder for 12 weeks period and also reported that feed consumption and feed efficiency were not affected by the diets. Recently, Safaa (2007) indicated that laying hen production performance was not affected by 2.0% garlic addition.…”
Section: Feed Intake and Egg Productionmentioning
confidence: 96%
“…According to Reddy et al (1991), egg production and feed efficiency were not affected during or at the end of eight weeks of feeding garlic oil to the Babcock layer. Canogullari et al (2009) fed layer diets containing 0, .5, 1 and 2% garlic powder for 12 weeks period and also reported that feed consumption and feed efficiency were not affected by the diets. Recently, Safaa (2007) indicated that laying hen production performance was not affected by 2.0% garlic addition.…”
Section: Feed Intake and Egg Productionmentioning
confidence: 96%
“…The reduction of cholesterol by cabbage corresponds to earlier reports where other natural plant materials have been used. For instance, Canogullari et al (2010) reported that garlic powder and thyme successfully reduced cholesterol levels in birds.…”
Section: Body Mass Index Effect Of Graded Levels Of Cabbage Within Gementioning
confidence: 99%
“…Their positive effect is demonstrated mainly on growth and egg productive performance, quality egg traits, differencial blood count and immunity response (Dorhoi et al, 2006;Canogullari et al, 2009Canogullari et al, , 2010Ghasemi et al, 2010;Mohebbifar and Torki, 2010;Navid et al 2014). There are many evidence to suggest that they may have beneficial influence on useful gut microflora altogether with inhibitory effects on pathogenic and conditionally pathogenic bacteria -clostridia, colibacteria, salmonellae etc.…”
Section: Introductionmentioning
confidence: 99%